Cost-effectiveness of a cardiovascular polypill strategy (aspirin, atorvastatin, ramipril) for the secondary prevention of cardiovascular disease based on real life improvement in risk factor control. (11th May 2021) - Rubio, G; Araujo, F; Aguiar, C; Carcedo, D; Abreu-Oliveira, TP; Paz, S; Castellano, JM
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Ferrer Internacional Background: The cardiovascular (CV) polypill has consistently demonstrated cost-effectives in decreasing the risk of CV disease in patients in secondary prevention. Previous pharmacoeconomic studies addressed improvements in adherence as a driver of health gains. This economic assessment focuses on the implications of improved control of risk factors with the polypill as observed in clinical practice. Purpose: To assess the cost-effectiveness of a fixed-dose combination polypill (ASA 100mg, atorvastatin 20/40mg, ramipril 2.5/5/10mg) strategy for the secondary prevention of CV and cerebrovascular events in adults with a history of coronary heart disease (CHD) or stroke compared to usual care with monocomponents. Methods: A Markov cost-effectiveness model (1-year cycles; 4 health states: stable disease, subsequent CHD, subsequent stroke, death; payer perspective; direct medical costs; lifetime horizon; 4% discount rate) based on changes in CV risk factors (total cholesterol, 18.3% reduction; high density lipoprotein cholesterol, 2.1% increment; systolic blood pressure, 11.46% reduction) obtained from a real-life effectiveness study was set for Portugal. The probability of transition between health states was based on the SMART risk equation. Cost-effectiveness was calculated for two cohorts (n = 1, 000) of secondary prevention patients with previous CHD or stroke. Systematic reviews, Portuguese registries, mortality tables and official reports were searched to identify effectiveness, epidemiological, costs and utility data. Outcomes were costs (€, 2020) per life year (LY) and Quality Adjusted LY (QALY) gained. One-way (OWA) and probabilistic (PSA) sensitivity analyses tested consistency. Assumptions were validated by experts. Results: In the CHD cohort, the incremental cost-effectiveness ratio for the polypill strategy (ICER) is 2, 402 €/LY and the incremental cost-utility ratio (ICUR) is 2, 328 €/QALY. Incremental cost reaches 278, 927 € (polypill, 13, 198, 506 €; monocomponents: 12, 919, 579 €) with less subsequent CV events (552.31 vs 641.88) and CV deaths (102.4 vs 118.68). Assuming a willingness-to-pay (WTP) threshold of 30.000 €/QALY gained, the PSA shows a 81.4% probability for the polypill to be cost-effective and 39.1% chances to be costs saving compared to usual care. In the stroke cohort, the ICER is 386 €/LY and the ICUR is 553 €/QALY. Incremental costs are 34, 178 € (polypill, 10, 138, 807 €; monocomponents: 10, 104, 629 €) with less subsequent CV events (481.99 vs 564.50) and CV deaths (101.00 vs. 117.23) with the polypill. There is a 75.9% probability for the polypill to be cost-effective and 49.5% chances to be costs saving. Conclusion: The CV polypill is a cost-effective secondary prevention strategy compared to usual care with monocomponents. Its ICER is well below acceptable thresholds in both CV and cerebrovascular disease patients. It reduces the number of recurrent events at a moderately higher cost compared to monocomponents.